Targeting progesterone receptors in newborn males and females: From the animal model to a new perspective for the treatment of apnea of prematurity? - Bairam, Aida; Boukari, Ryma; Joseph, Vincent (Respiratory physiology & neurobiology, 2019)
•We review the respiratory effects of progesterone in newborns rats.•Progesterone acts through nuclear and membrane receptors.•New data show that progesterone receptors have age- and sex-specific effects.•These data might help design new therapeutic approaches for apnea of prematurity. The steroid hormone progesterone is well-known for its role in neuroprotection, in the pre- and postnatal brain development, and is also recognized as a potent respiratory stimulant that reduces the frequency of sleep apnea in adult female subjects. Over the past few years, we have used newborn rats or mice to provide convincing evidence that the respiratory effect of progesterone involves a balance between excitation mediated by progesterone receptors, and an inhibition due to the fast conversion of progesterone to allopregnanolone, a positive allosteric modulator of GABAA receptors. This review focuses on the sex- and age- specific roles of nuclear and membrane progesterone receptors (nPR or mPR), and highlight the clinical potential of these receptors for the treatment of apnea of prematurity. We present original data showing that in newborn rats, selective nPR or mPR agonists are more efficient to reduce apnea frequency at postnatal days 12 than at postnatal day 1, and appear more efficient in males than in females. Furthermore, new results obtained by using intra-cisternal injection of specific siRNA targeting mPRα, mPRβ (two mPR with high brain expression) or nPR suggest that mPRβ regulates the stability of the breathing pattern in males, while effects of nPR appear in females. While several important questions remain to be addressed before a safe clinical use could be proposed, these results highlight the potential role of these drugs as complementary, and sex-specific tools for the treatment of apnea in preterm neonates.